Double-stranded RNA is pathogenic in Drosophila models of expanded repeat neurodegenerative diseases. - Lawlor, K.T.; O'Keefe, L.V.; Samaraweera, S.E.; van Eyk, C.L.; McLeod, C.J.; Maloney, C.A.; Dang, T.H.; Suter, C.M.; Richards, R.I. (Human Molecular Genetics, 2011)
The pathogenic agent responsible for the expanded repeat diseases, a group of neurodegenerative diseases that includes Huntington's disease is not yet fully understood. Expanded polyglutamine (polyQ) is thought to be the toxic agent in certain cases, however, not all expanded repeat disease genes can encode a polyQ sequence. Since a repeat-containing RNA intermediary is common to all of these diseases, hairpin-forming single-stranded RNA has been investigated as a potential common pathogenic agent. More recently, it has become apparent that most of the expanded repeat disease loci have transcription occurring from both strands, raising the possibility that the complementary repeat RNAs could form a double-stranded structure. In our investigation using Drosophila models of these diseases, we identified a fortuitous integration event that models bidirectional repeat RNA transcription with the resultant flies exhibiting inducible pathology. We therefore established further lines of Drosophila expressing independent complementary repeat RNAs and found that these are toxic. The Dicer pathway is essential for this toxicity and in neuronal cells accounts for metabolism of the high copy number (CAG.CUG)(100) double-stranded RNAs down to (CAG)(7) single-stranded small RNAs. We also observe significant changes to the microRNA profile in neurons. These data identify a novel pathway through which double-stranded repeat RNA is toxic and capable of eliciting symptoms common to neurodegenerative human diseases resulting from dominantly inherited expanded repeats.